PENGARUH KEPERCAYAAN DALAM MEDIASI PERCEIVED OF RISK TERHADAP NIAT BERBELANJA ONLINE DI MEDIA SOSIAL INSTAGRAM (STUDI PADA WANITA DI KOTA PADANG) - Fenisi Resty; Mayroza Wiska (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
One of the effective social media for online shopping is Instagram. Shopping online on social media Instagram, consumers only see products in photos, catalogs and videos without knowing the quality of the product, because buyers do not meet directly with the seller only through gadgets, cellphones or computers. Trust is the main capital in online shopping. This research was conducted to examine the influence of trust in perceived of risk mediation on the intention to transact online shopping on social media Instagram. The sample of this research is 120 women in Padang City. The research method uses quantitative analysis techniques using a questionnaire, sampling method is non-probability sampling using purposive sampling tectic. This research uses SmartPLS version 3.0 software.